Detection and typing of Clostridium perfringens from retail chicken meat parts - Guran, H. S.; Oksuztepe, G. (Wiley, 2013)
The objectives of the present work were to investigate the presence of Clostridium perfringens in chicken meat parts (breast, wing, drumstick and leg quarter) by culture methods and to detect the cpa, cpb, etx, iA, cpe and cpb2 toxin genes by multiplex PCR. A total of 200 samples, the raw chicken breasts (n: 50), wings (n: 50), drumsticks (n: 50) and leg quarters (n: 50), were collected from various retail stores. Our results demonstrated that 47 of 50 wing samples (94%), 40 of 50 leg quarter samples (80%), 34 of 50 drumstick samples (66%) and 33 of 50 breast samples (66%) were found to be contaminated with Cl.perfringens. 558 positive isolates obtained from these samples were identified as Cl.perfringens based on the microscopic examination and biochemical tests. It was detected that 545 (97 center dot 6%) of 558 Cl.perfringens isolates carried only cpa toxin gene (type A), 12 (2 center dot 1%) of them carried both cpa and cpb2 toxin gene (type A-cpb2), one (0 center dot 1%) of them carried both cpa and cpe toxin genes (type A-cpe), according to the multiplex PCR results, targeted cpa, cpb, cpb2, cpe, etx and iA genes. Significance and Impact of the Study This study is the first report of detection of cpe and cpb2 toxin genes in Clostridium perfringens isolated from chicken meats in Turkey. The multiplex PCR protocol described in this study is useful for rapid detection of Clostridium perfringens toxin genes simultaneously in one-step PCR.
Keywords: chicken meat parts; Clostridium perfringens; multiplex PCR; prevalence; toxin genes